2007
DOI: 10.1016/j.gca.2007.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Redistribution of REE, Pb and U by supergene weathering studied from in-situ isotopic analyses of the Bangombé natural reactor, Gabon

Abstract: The isotopic analyses of rare earth elements (REE), Pb and U in several kinds of minerals from the clay and black shale layers above the Bangombé natural reactor, Gabon, were performed using a sensitive high-resolution microprobe (SHRIMP) to investigate the migration and retardation processes of fission products released from the reactor. REE isotopic data of the secondary minerals found in clays and black shales show that most of fission products were effectively trapped in the clays and not distributed into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 17 publications
(44 reference statements)
0
13
0
Order By: Relevance
“…5a and b) have the large variation of the 238 U/ 206 Pb data from 0.23 to 38.8 and the small variation of 207 Pb/ 206 Pb data (most values are near 0.11-0.12), which suggests the existence of independent U and Pb sources that have migrated into zircon grains. Judging from the 207 Pb/ 206 Pb ratios commonly observed especially in low U/Pb parts of the zircon, the migrated Pb into the zircon was probably derived from the same source as that which formed the galena above the Bangombé reactor zone (Kikuchi et al, 2007). The previous studies revealed that the U and Pb originated 2.05-Ga old uraninite have occurred a large chemical fractionation under recent severe weathering within one million years (Hidaka et al, 2005;Kikuchi et al, 2007).…”
Section: Resultsmentioning
confidence: 85%
See 4 more Smart Citations
“…5a and b) have the large variation of the 238 U/ 206 Pb data from 0.23 to 38.8 and the small variation of 207 Pb/ 206 Pb data (most values are near 0.11-0.12), which suggests the existence of independent U and Pb sources that have migrated into zircon grains. Judging from the 207 Pb/ 206 Pb ratios commonly observed especially in low U/Pb parts of the zircon, the migrated Pb into the zircon was probably derived from the same source as that which formed the galena above the Bangombé reactor zone (Kikuchi et al, 2007). The previous studies revealed that the U and Pb originated 2.05-Ga old uraninite have occurred a large chemical fractionation under recent severe weathering within one million years (Hidaka et al, 2005;Kikuchi et al, 2007).…”
Section: Resultsmentioning
confidence: 85%
“…Judging from the 207 Pb/ 206 Pb ratios commonly observed especially in low U/Pb parts of the zircon, the migrated Pb into the zircon was probably derived from the same source as that which formed the galena above the Bangombé reactor zone (Kikuchi et al, 2007). The previous studies revealed that the U and Pb originated 2.05-Ga old uraninite have occurred a large chemical fractionation under recent severe weathering within one million years (Hidaka et al, 2005;Kikuchi et al, 2007). Because the 207 Pb/ 206 Pb data show a small variation of ~0.12 corresponding to the mean age of 1959 ± 12 Ma selected from 23 of 46 as the best of the zircon analyses, U and Pb of these two components were originated from 2.05-Ga old uraninite and migrated into zircon grains independently under the recent severe weathering.…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations